Molecular Characterisation of Vancomycin-Resistant Enterococcus faecium Isolates Belonging to the Lineage ST117/CT24 Causing Hospital Outbreaks - Lisotto, Paola; Couto, Natacha; Rosema, Sigrid; Lokate, Mariëtte; Zhou, Xuewei; Bathoorn, Erik; Harmsen, Hermie J. M.; Friedrich, Alexander W.; Rossen, John W. A.; Chlebowicz-Fliss, Monika A. (Frontiers in Microbiology, 2021)
Background: Vancomycin-resistant Enterococcus faecium (VREfm) is a successful nosocomial pathogen. The current molecular method recommended in the Netherlands for VREfm typing is based on core genome Multilocus sequence typing (cgMLST) however, the rapid emergence of specific VREfm lineages challenges distinguishing outbreak isolates solely based on their core genome. Here, we explored if a detailed molecular characterisation of mobile genetic elements and accessory genes could support and expand the current molecular typing of VREfm isolates sharing the same genetic background, enhancing the discriminatory power of the analysis. Materials/methods: The genomes of 39 VREfm and 3 vancomycin-susceptible E. faecium (VSEfm) isolates belonging to ST117/CT24, as assessed by cgMLST, were retrospectively analysed. The isolates were collected from patients and environmental samples from 2011 to 2017, and their genomes were analysed using short-read sequencing. Pangenome analysis was performed on de novo assemblies, which were also screened for known predicted virulence factors, antimicrobial resistance genes, bacteriocins and prophages. Two representative isolates were also sequenced using long-read sequencing, which allowed a detailed analysis of their plasmid content. Results: The cgMLST analysis showed that the isolates were closely related, with a minimal allelic difference of 10 between each cluster's closest related isolates. The vanB-carrying transposon Tn1549 was present in all VREfm isolates. However, in our data, we observed independent acquisitions of this transposon. The pangenome analysis revealed differences in the accessory genes related to prophages and bacteriocins content, while a similar profile was observed for known predicted virulence and resistance genes. Conclusions: In the case of closely related isolates sharing a similar genetic background, a detailed analysis of mobile genetic elements and the integration point of the vanB-carrying transposon allows to increase the discriminatory power compared to the use of cgMLST alone. Thus, enabling the identification of epidemiological links among hospitalised patients.